Imperative clauses in generative grammar : studies in honour of Frits Beukema - Beukema, F. H. (Frits H.); Wurff, Wim van der (Linguistik aktuell ;, 2007)
This volume contains ten articles exploring a wide range of issues in the analysis of the imperative clause from a generative perspective. The language data investigated in detail in the articles come from Dutch, English, German, (old) Scandinavian, Spanish, and South Slavic; there is further significant discussion of data from other Germanic and Romance languages. The phenomena addressed (in several cases in more than one article, leading to some lively debate about contentious issues) include the following: the nature and interpretation of imperative subjects; the properties of participial i.